STRATEGI PEMASARAN PARIWISATA DALAM RANGKA MENINGKATKAN DAYA TARIK KUNJUNGAN WISATAWAN DI KABUPATEN SUMBAWA - Dika Saputra; Binar Dwiyanto Pamungkas (Samalewa: Jurnal Riset & Kajian Manajemen, 2023)
This study aims to determine the tourism marketing strategy in order to increase the attractiveness of tourist visits in the Sumbawa District. This type of research is descriptive research that aims to describe tourism marketing strategies in order to increase the attractiveness of tourist visits in Sumbawa District. The type of data used is qualitative data obtained directly from primary sources through interviews. The informants in this study were people who were considered to know about the condition of tourism in Sumbawa Regency, which consisted of 7 tourist object managers. Data was collected using the interview method which will then be analyzed using the SWOT analysis technique. The results showed that the total IFE score was 0.45 and the EFE score was 0.70. Thus, the position of the Mata Jitu tourist attraction in Sumbawa Regency is in quadrant I which is a favorable situation so that the strategy implemented in order to have competitiveness to increase tourist visits is to support aggressive growth policies (growth oriented strategy). This strategy signifies a strong state, by utilizing all the strengths and opportunities it has to overcome all the weaknesses and threats it faces so that the number of tourist visits can increase and maximum profits can be obtained.